Crystalline Sponge Method by Three-Dimensional Electron Diffraction - Chen, Pohua; Liu, Yang; Zhang, Chaochao; Huang, Fei; Liu, Leifeng; Sun, Junliang (Frontiers in Molecular Biosciences, 2022)
The crystalline sponge method has shown to be a novel strategy for the structure determination of noncrystalline, oily, or trace amount of a compound. A target compound was absorbed and oriented orderly in the pregrown porous crystal for x-ray diffraction analysis. However, the diffusion in the micron-sized crystals is rather difficult. Lots of trial-and-error experiments are needed to optimize the guest-soaking process and to improve data quality. Nanocrystals are better in diffusion, yet it could not conduct a single crystal x-ray diffraction (SCXRD) analysis. Three-dimensional electron diffraction (3D-ED) is a powerful diffraction tool for the structure determination of small crystals. In this work, we successfully carried out the crystalline sponge method by 3D-ED technique using {(ZnI2)3-[2,4,6-tris(4-pyridyl)-1,3,5-triazine]2·x(guest)}n (1-Guest) porous complex nanocrystals. On account of the better diffuse ability of nanocrystals, the time needed for solvent exchange and guest soaking protocols are shortened 50-fold faster versus the original protocol. The crystal structure of the crystalline sponge incorporated with three different guests was fully resolved using a merged dataset. The structure model was identical to previously reported ones using x-ray, showing that the accuracy of the 3D-ED was comparable with SCXRD. The refinement results can also give the precise occupancy of the guest molecule soaked in the porous crystal. This work not only provides a new data collection strategy for crystalline sponge method but also demonstrates the potential of 3D-ED techniques to study host-guest interaction by solving the fine structure of porous material.